2010
DOI: 10.1111/j.1751-0813.2010.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of tidal breathing flow volume loop in dogs with tracheal masses

Abstract: TBFVL is a non-invasive technique that is easy to perform and well tolerated by dogs. In the absence of abnormalities detected by routine diagnostic evaluations and arterial blood gas analysis in dogs with intratracheal masses, the TBFVL contributes to the definition of the physiologic status of the airways at the time of testing, and results suggests that these dogs breathe quite normally when they are calm and non-dyspnoeic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Despite the fact that TBFVL analysis has been used in veterinary medicine since 1986, there are no studies that have aimed specifically to develop a database of reference values for healthy dogs . In an attempt to bypass this problem, all existing reports use their own normal reference population . The present study aimed to take a fundamental step in the development of a database.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the fact that TBFVL analysis has been used in veterinary medicine since 1986, there are no studies that have aimed specifically to develop a database of reference values for healthy dogs . In an attempt to bypass this problem, all existing reports use their own normal reference population . The present study aimed to take a fundamental step in the development of a database.…”
Section: Discussionmentioning
confidence: 99%
“…This can be observed in both phases of respiration . However, it has been reported that such changes are not always detected in dogs with airway obstruction, probably because the flow depends on multiple factors such as V T , time, pressure, effort and resistance . Additionally, diseases that can influence intrathoracic pressure during both respiratory phases may cause the flow‐related inspiratory and expiratory parameters to have values within the reference ranges .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tidal breathing flow-volume loops in upper airway obstruction of infants[56,57]and dogs[33-36,58] show characteristic flattening of the inspiratory limb. Although the shape of the flow-volume loops from GRMD dogs was consistent with upper airway obstruction, the expiration limb was consistently abnormal rather than the inspiratory limb, when compared with the control dog population.…”
Section: Discussionmentioning
confidence: 99%